The Right to Health Information in Psychiatry in Spain (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This study addresses the right to health information in the Spanish legal system from a constitutional point of view, with special attention to the field of psychiatry. Firstly, it analyses the constitutional basis of the information provided in the doctor–patient relationship and the legal regime provided for in the Spanish Law on Patient Autonomy. Finally, it studies more specifically the information of psychiatric patients at the state level and the only specific law that exists at the autonomous level, in the Community of La Rioja.
Keywords: Health; information; psychiatry; informed consent; doctor-patient relationship